Bridging Faith Boundaries: Perspectives of Islamic Religious Education Teachers on Visits to Non-Muslim Places of Worship - Fauzi, Umar Hamzah; Nurhidayat, Deden (Bestari, 2025)
This study investigates the attitudes of Islamic Religious Education (PAI) teachers in Ciamis District, Indonesia, concerning student visits to non-Muslim places of worship. Employing a qualitative research methodology, specifically through in-depth interviews, we sought to capture the nuanced perspectives of these educators. Our findings reveal that the preponderant majority of teachers hold a positive outlook on such visits. They generally permit these educational excursions, provided that the visits are explicitly geared towards educational objectives and that students are deemed sufficiently mature to grasp religious diversity and are prepared to foster peaceful coexistence. These insights are particularly salient for educational institutions, offering a tangible framework for designing and implementing interfaith engagements that extend beyond mere theoretical instruction. Critically, this research underscores the potential of these carefully curated visits to cultivate a profound sense of tolerance and mutual understanding among students towards faiths distinct from their own. More broadly, the findings carry significant implications for curriculum development in religious education, suggesting a pedagogical shift towards experiential learning that directly addresses issues of religious pluralism and social harmony. Furthermore, they highlight the pivotal role of teacher disposition in shaping student attitudes toward diversity, offering a compelling case for professional development initiatives that support nuanced approaches to religious tolerance in increasingly diverse societies.